A new dimension of simplified science communication: the easiness effect of science popularization in animated video abstracts - Salzmann, Sara; Walther, Charlotte; Kaspar, Kai (Frontiers in Psychology, 2025)
IntroductionA common approach to make scientific information more accessible for the broader public, is making it easier to understand and translating it into more appealing formats, like short and entertaining online videos. However, simplifying scientific content can have negative impact on consumers, as it can lead to the so-called easiness effect, a cognitive bias which can include an overestimation of one’s own competencies. In the context of scientific studies, this bias has previously only been demonstrated by comparing text-based scientific abstracts with easier-to-understand plain language summaries (PLS). With several unsuccessful approaches in research to reduce the easiness effect, a promising new method might be using debiasing videos as they have been shown to reduce cognitive biases in other contexts. The present study expands the research by exploring the easiness effect in animated video abstracts and investigates whether a debiasing video can reduce it.MethodThis experiment realized a 2 (video abstract type: PLS versus scientific abstracts) × 2 (debiasing video: shown versus not shown) between-participants design. Overall, 179 participants received four abstracts and rated (1) study comprehensibility, (2) perceived study credibility, (3) confidence in one’s ability to evaluate the study, and (4) perceived ability to make decisions without further information. Also, intended consumer reactions (knowledge-enhancing and social media reactions) were collected.ResultsAnimated PLS, compared to animated scientific abstracts, actually enhanced comprehensibility of scientific content. This effect was accompanied by a significant easiness effect, as PLS were perceived as more credible and they produced a higher confidence in the recipients’ perceived ability to evaluate the study. No differences in consumer reactions were observed between abstract types. Also, the video-based debiasing intervention did not affect study evaluation.DiscussionThe easiness effect can be reliably generated in video abstracts and it is very robust, as it persists even if a debiasing intervention is carried out beforehand. This study underscores the need for responsible communication strategies in science popularization and shifts the focus to the increasingly popular video abstracts. The results provide a valuable starting point for further research on how video-based science communication can be optimized to convey scientific information effectively.